Clinical Holistic Medicine: Use and Limitations of the Biomedical Paradigm - Soren Ventegodt; Mohammed Morad; Eytan Hyam; Joav Merrick (The Scientific World Journal)
The biomedical paradigm is so convincing from a biochemical point of view, and highly efficient in many cases of acute medical problems and emergencies, but unfortunately most patients do not get much better only treated with drugs; they need to do something about their lives themselves. It is highly important for the modern physician to understand the strengths and weaknesses of the modern biomedical paradigm, to understand when and when not to administer drugs to their patients. Often a symptom can be eliminated for a while with drugs, but this is not always good as the patient might need to learn to study the imbalances in life that cause the disturbances and symptoms. For the elderly patient, sometimes life can be extended in spite of the subjective fact that life has come to its end. Sometimes treatment with a drug can teach the patient that quality of life is the responsibility of the physician and not the patient. This learned attitude can give the patient problems later or make them less active in helping themselves (responsibility transfer in the wrong direction).This paper gives a number of examples where medical drugs really are the treatment of choice in general practice and some more doubtful examples of using of the biomedical paradigm.